Extending Feistel structure to DNA Cryptography. (4th July 2015) - Kaundal, Ashish Kumar; Verma, A. K.
Abstract: DNA cryptography is a novel field being taken up by the researcher community for research now days in order to have secure communication on a network. This technique is inspired from biological science, in which DNA is used as an information carrier from one generation to another. DNA cryptography is proposed for a secure end to end communication due to the vast parallelism and extra ordinary information density that are inherent in any DNA molecule. In this paper previous algorithm based on DNA cryptography is enhanced in terms of its security parameter by incurring feistel inspired structure in it. This adds some sort of confusion and diffusion, which makes it complex enough that it restricts the adversary to perform any kind of brute force attack. Encryption and decryption time is also compared on the basis of variable plaintext size.